(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Securinega virosa is synonymous to Flueggea virosa, it could be used interchangeably. Many studies have shown that Securinega virosa is a natural source for alkaloids, these alkaloids are term Securinega alkaloids. Though, many other compounds have been isolated from this medicinal plant i.e. flavonoids, phenolics and terpenes. Alkaloids have been established as a chemotaxonomy marker for this species since this medicinal plant is a component in most herbal products. This review seeks to establish the friendly connection between this plant and terpenoids by explicitly stating the pharmacological importance of this class of compounds in this species, which suggest the nature and property of terpenoids and also giving an update on the isolated terpenoids (about fourty-one (41) isolated so far). Also to clarify that beside alkaloids compounds, terpenoids could be used also as a chemotaxomic marker for this plant.